TRANSFORMASI TEKNOLOGI INFORMASI DI ERA DIGITAL: PELUANG, TANTANGAN, DAN IMPLEMENTASI PADA BERBAGAI SEKTOR - Ridwan Ridwan; Solly Aryza; Zulham Sitorus; Muhammad Iqbal (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Information technology transformation has become a major driver of change across various sectors, including education, business, government, healthcare, and industry. The rapid advancement of digital technologies such as cloud computing, Artificial Intelligence (AI), the Internet of Things (IoT), big data, and modern communication technologies has improved operational efficiency, service quality, and data-driven decision-making within organizations. This study aims to analyze the opportunities, challenges, and implementation of information technology across multiple sectors in the digital era. The research employed a Systematic Literature Review (SLR) by examining national and international scientific publications published between 2022 and 2026. The findings indicate that information technology implementation significantly enhances productivity, innovation, transparency, and organizational competitiveness when supported by effective governance, adequate digital infrastructure, and competent human resources. Nevertheless, digital transformation continues to face challenges related to cybersecurity, personal data protection, digital inequality, infrastructure limitations, and insufficient digital literacy. Therefore, integrated, adaptive, and sustainable digital transformation strategies are required to maximize the benefits of information technology for organizations and society. Keywords: Digital Transformation, Information Technology, Artificial Intelligence, Internet of Things, Systematic Literature Review   Abstrak: Transformasi teknologi informasi telah menjadi pendorong utama perubahan di berbagai sektor, termasuk pendidikan, bisnis, pemerintahan, kesehatan, dan industri. Perkembangan teknologi digital seperti cloud computing, Artificial Intelligence (AI), Internet of Things (IoT), big data, dan teknologi komunikasi modern telah meningkatkan efisiensi operasional, kualitas layanan, serta kemampuan organisasi dalam pengambilan keputusan berbasis data. Penelitian ini bertujuan menganalisis peluang, tantangan, dan implementasi teknologi informasi pada berbagai sektor di era digital. Metode penelitian menggunakan Systematic Literature Review (SLR) dengan mengkaji artikel ilmiah nasional dan internasional yang dipublikasikan pada periode 2022–2026. Hasil kajian menunjukkan bahwa penerapan teknologi informasi memberikan dampak positif terhadap peningkatan produktivitas, inovasi, transparansi, dan daya saing organisasi apabila didukung oleh tata kelola yang efektif, infrastruktur digital yang memadai, serta sumber daya manusia yang kompeten. Namun, implementasi transformasi digital masih menghadapi tantangan berupa keamanan siber, perlindungan data pribadi, kesenjangan digital, keterbatasan infrastruktur, dan rendahnya literasi digital. Oleh karena itu, diperlukan strategi transformasi digital yang terintegrasi, adaptif, dan berkelanjutan agar pemanfaatan teknologi informasi mampu memberikan nilai tambah bagi organisasi dan masyarakat. Kata kunci: Transformasi Digital, Teknologi Informasi, Artificial Intelligence, Internet of Things, Systematic Literature Review.